Fluorescently Labeled Bacteria as a Tracer to Reveal Novel Pathways of Organic Carbon Flow in Aquatic Ecosystems - Šimek, Karel; Sirova, Dagmara (Journal of visualized experiments, 2019)
Elucidating trophic interactions, such as predation and its effects, is a frequent task for many researchers in ecology. The study of microbial communities has many limitations, and determining a predator, prey, and predatory rates is often difficult. Presented here is an optimized method based on the addition of fluorescently labelled prey as a tracer, which allows for reliable quantitation of the grazing rates in aquatic predatory eukaryotes and estimation of nutrient transfer to higher trophic levels.
Keywords: Predatory Behavior; Tetrahymena; Food Chain; mikrobiota; predátorské chování; Water Microbiology; řeky; Microbiota; zvířata; Eukaryota; Rivers; Carbon; Czech Republic; mikrobiologie vody; Bacteria; Animals; uhlík; Česká republika; potravní řetězec